Copper metabolism in the plaice, Pleuronectes platessa (L.) - Syed, M.Arif; Coombs, Thomas L. (1982)
Copper metabolism in a teleost, the plaice, Pleuronectes platessa (L.) from a natural environment has been studied. Distribution in the various tissues of the metal and of five key copper-dependent enzymes: ceruloplasmin EC 1.16.3.1; Superoxide dismutase EC 1.15.11; tryptophan oxygenase EC 1.13.1.12; cytochrome oxidase EC 1.9.3.1 and monoamine oxidase EC 1.4.3.4 have been determined. The copper distribution was found to be similar to that in mammals with the greatest concentrations in the brain and heart. Distribution of the copper enzymes is also similar to that found in mammals. A preliminary characterization of the copper enzymes showed that plaice cytochrome oxidase has a pH maximum 2 pH units more alkaline than the mammalian enzyme and that plaice tryptophan oxygenase is more sensitive to heat denaturation than the mammalian enzyme. The present data form a base-line against which studies on factors affecting the copper metabolism in a teleost can be assessed. © 1982.